The impact of high intensity training and sports on recipients of solid organ transplants: a narrative review - Kayeye, A.; Triantafyllou, I.; Mathur, S.; Janaudis-Ferreira, T. (Frontiers in Sports and Active Living, 2024)
Objectives High intensity exercise in individuals post solid organ transplant (SOT) remains a largely understudied phenomenon, with potential risks and benefits. Additionally, the optimal training protocols are still unclear. This narrative review aimed to explore the impact of high-intensity exercise training and strenuous sports on solid organ transplant recipients (SOTRs). Methods We conducted a narrative review of intervention studies of any design that included high-intensity exercise training and cross-sectional studies of strenuous sports and activities. Additionally, we reviewed individual reports documenting post-SOT performance at highly competitive or physiological levels. We used MEDLINE to search for relevant articles followed by a manual search for additional articles. Data were extracted and results were summarized. Results High-intensity and strenuous exercise appears to be safe among stable SOTRs. High-intensity protocols consistently demonstrated improvements in VO2peak and a reduction in coronary artery disease prevalence, though findings related to body composition, health-related quality of life outcomes, and cardiovascular exercise variables were inconsistent. Pre-transplant athletes showcase notable achievements and physiological adaptations post-transplantation, highlighting the capacity for athletic performance among this population. However, caution is warranted in interpreting the findings from these studies due to limitations in generalizability and other methodological limitations. Conclusion As evidenced by current literature, high intensity exercise emerges as a promising exercise method for safely improving various physiological parameters, and reducing the prevalence of coronary heart disease in SOTRs. It can induce similar or greater effects to moderate intensity exercise, however follow-up studies indicate low retention. Further research of higher methodological rigor is warranted in this field to advance understanding, and to guide evidence-based practice.